Model of the relationship between egg weight and the external quality of Pengging duck (Anas plathyrynchos) - Hartati, Lilis; Sihite, Mikael; Bramantiar, Sambodo Ilham (Jurnal Ilmu Peternakan Terapan, 2024)
This research was designed to analyze the relationship between egg weight and the external quality of Pengging duck eggs. The method used in the research was quantitative observational.  Samples of Pengging Duck eggs were taken from the Banyubiru Satker Center, Semarang Regency, totaling 250 eggs. The variables measured include egg weight, egg length and egg width, egg length and width circumference, egg volume, egg specific gravity, egg index and egg circumference index. The analysis used was regression analysis with egg weight as the dependent variable (Y) and external egg quality (egg length, etc.) as the independent variable (X). Relationship models obtained for egg length-egg weight (Y=13.872x-11.994), egg width-egg weight (Y=21.392x-31.395), egg circumference index-egg weight (Y=1.9624x+33.523), width circumference-egg weight (Y=3.8527x+8.4576), egg specific gravity-egg weight (Y=-8.931x+76.308), egg index-egg weight (Y=-8.166x+72.718), egg circumference index-egg weight (Y=-7.339x+72.69). It could be concluded that the length, width, length perimeter, width perimeter, and specific gravity of the eggs were found to be highly related to egg weight of Pengging Duck.